The surface area is length times width plus length. Then you find the square root of the width divided by two and then squared. You add this to the height squared plus the width. The width is multiplied by the square root of 1/2 squared plus the height squared.
still 1The square root of 1 is plus or minus 1. √1 = ± 1 The reason is that 12 = 1 and -12 = 1. (Either 1 squared or minus 1 squared equals one.)
1/2 times (1 - square root of 5), or 1/2 times (1 + square root of 5)
It is: 1+1+8 = 10
X2+5x-6. a=1, b=5, and c=-6 The formula is: -b plus or minus the square root of b squared minus 4ac all over 2a. -b+square root of b2-4ac ---- 2a -5 plus or minus the square root of 5 squared minus 4(1)(-6) -5 plus or minus the square root of 25-4(-6) -5 plus or minus the square root of 25+24 -5 plus or minus the square root of 49 -5 plus or minus 7 Here is where you split into two different answers: Number 1: -5 plus 7= 2 Number 2: -5 minus 7= -12 Your answer is X=2, -12
X= plus or minus 1
(x + (1 - 2i))(x + (1 + 2i)) where i is the imaginary square root of -1
That doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (-1 plus or minus the square root of -3) divided by 2.x = -0.5 + 0.8660254037844386ix = -0.5 - 0.8660254037844386iwhere i is the square root of negative one.
Ordinarily, the square root of -70 does not exist since a positive number squared or a negative number squared results in a positive number. If complex numbers are permitted, then the square root of -70 is i√70 ~= 8.367i where i is the imaginary square root of -1 such that i2 = -1.
i is an imaginary number which equals the square root of -1. i squared is simply -1.
so x squared + 12 = 0 so xsquared = -12 which lands you in the realm of imaginary numbers. The square root of -12 is 2i root 3 where i is the imaginary sqrt of -1.
The square root of 1 is 1. We can check it by looking at the equation 1 x 1 = 1 which shows that 1 squared is equal to 1.
x2+2x=9 we can complete the square or use the quadratic formula. Let's complete the square. add 2/2=1 to both sides and we ahve x2+2x+1=10 now factor the left side and use the square root property (x+1)2=10 so x+1= plus of minus the square root of 10 x=- 1+ or - square root of 10 using the quadratic formula we have a=1, b=2 and c=-9 so [-2+ or - (square root of (4+36))]/2= -1 + or - square root of 10 as we had before.
That can be true when "x" and "y" are both zero, or both 1.
sqrt(x3 + x2) = x*sqrt(x+1) and that cannot be simplified further.
(x - i)(x + i) where i is the imaginary square root of negative one
it is 4i, where i is the object such that i squared =-1
the integral of the square-root of (x-1)2 = x2/2 - x + C
It'll be a complex number, denoted by 7i, where the number i is defined to be equal to the square root of -1.
A number that is squared is a number 49 is 7 because 7 squared is 7x7=49 square root of 1=1 4=2 9=3 and so on.
: x squared times square root of x : : = x^2 * x^(1/2) : = x^[2+(1/2)] : = x^[(4/2)+(1/2)] : = x^(5/2) : which is the same thing as : square root of (x raised to the 5th power)
-3 squared = 9. The square root of -9 is 3i, i being the square root of -1
X^1/2 + Y^1/2 Essentially it is just the square root of x plus the square root of y, there's no real way of simplifying that.
I t doesn't! -3 squared = 9. The square root of -9 is 3i, i being the square root of -1, and that opens up a very complicated can of worms!